2002
DOI: 10.1111/1467-9450.00302
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for children with lesbian or gay parents. A review of studies from 1978 to 2000

Abstract: Twenty-three empirical studies published between 1978 and 2000 on nonclinical children raised by lesbian mothers or gay fathers were reviewed (one Belgian/Dutch, one Danish, three British, and 18 North American). Twenty reported on offspring of lesbian mothers, and three on offspring of gay fathers. The studies encompassed a total of 615 offspring (age range 1.5-44 years) of lesbian mothers or gay fathers and 387 controls, who were assessed by psychological tests, questionnaires or interviews. Seven types of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
10

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(94 citation statements)
references
References 48 publications
3
81
0
10
Order By: Relevance
“…The lesbian family is often described as a new family form in the Western world (Anderssen, Amlie & Ytterøy, 2002;Bos, van Balen & van den Boom, 2005). Such claims definitely give a limited picture.…”
Section: Lesbian Families and Modern Family Theorymentioning
confidence: 99%
“…The lesbian family is often described as a new family form in the Western world (Anderssen, Amlie & Ytterøy, 2002;Bos, van Balen & van den Boom, 2005). Such claims definitely give a limited picture.…”
Section: Lesbian Families and Modern Family Theorymentioning
confidence: 99%
“…20 A large body of scientific literature demonstrates that children and adolescents who grow up with gay and/or lesbian parents fare as well in emotional, cognitive, social, and sexual functioning as do children whose parents are heterosexual. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Although the methodologic challenges are daunting in addressing phenomena as complex and multifactorial as children' s longterm developmental and psychosocial outcomes, the literature accumulated over more than 30 years, taken together, provides robust, reliable, and valid assurance about the well-being of children raised by parents of the same gender. 28,29 The first review of available data regarding the well-being of children living with lesbian or gay parents concluded that "While research on these topics is relatively new….there is no evidence that the development of children with lesbian and gay parents is compromised in any significant respect relative to that among children of heterosexual parents in otherwise comparable circumstances."…”
Section: Children's Developmental Trajectory and Psychological Outcomesmentioning
confidence: 99%
“…In the study done in 1983 the authors found that in terms of sexual preferences, stigmatization, gender role behaviour, behavioural adjustment and gender identity, there were no differences between the two groups comprising children aged 5 to 17 years, of whom the first group (37 children) lived in single-or two-parent lesbian families and the comparative group (38 children) lived with single-parent heterosexual mothers. The only difference between the two groups of children in 1983 was that more children of heterosexual mothers had symptoms of mental health problems than children from families with lesbian parents (Golombok & Tasker, 1996, Anderssen, Amlie & YitterØy, 2002. The research study conducted in 1997 showed no differences between the two compared groups (ibid.).…”
Section: What Do Longitudinal Research Studies and Meta-analyses Of Tmentioning
confidence: 99%